Professional Development and Quality in Early Childhood Education Comparative European Perspectives (Springer International Publishing, 2018)
This book provides a global overview of developments and discussion around the evaluation of quality of early childhood education environments, and the professional development of early childhood teachers, during the last decade. It reports on the Early Change project, a European-funded research project with the participation of six European countries: Cyprus, Denmark, Finland, Greece, Portugal, and Romania; and offers an in-depth view on the perspectives of early childhood teachers regarding their professional development and the quality of early childhood education environment. Additionally, it discusses the policies and educational framework supporting the professional development of early childhood teachers across Europe. Finally, it proposes an alternative way to integrate the use of observational rating scales of early childhood education environments' quality in teachers' professional development. Presenting up-to-date scholarly research on global trends, this is an easily accessible, practical, yet scholarly source of information for researchers, policy makers and practitioners.